TO WHAT EXTENT DOES THE VANCOMYCIN ASSAY CONTRIBUTE TO THE VARIABILITY IN VANCOMYCIN CONCENTRATION ESTIMATES IN NEONATES?. Issue 1 (14th December 2015) - Samardžić, J.; Smits, A.; Cossey, V.; Soldatović, I.; Bajčetić, M.; Anker, J. N. van den; Allegaert., K.
Abstract : *presenting author, supported by ERAWEB II scholarship for postdoctoral program at the KU Leuven, Belgium (2014–2015) Introduction: Vancomycin, a glycopeptide antibiotic, is frequently used for late onset sepsis (LOS) and catheter-related infection. Larger inter- and intra-patient variability, combined with a narrow therapeutic index, warrants therapeutic drug monitoring (TDM). However, large inter-individual variability in PK parameters in neonates is documented, only partly explained by covariates such as weight, age or serum creatinine (1, 2). In the current study, we focus on the potential impact of between assay differences for vancomycin (3) on the variability in its concentration in a single neonatal intensive care unit (NICU). Methods: Vancomycin TDM observations of neonates and young infants treated with intravenous vancomycin, mainly for (suspected) LOS (ie, >72 hours after birth), in the Leuven NICU, Belgium, between June 2011 and December 2014. Our patient population, consists of (pre)term neonates, inborn or transferred, in need of specialized care related to prematurity, infections, perinatal asphyxia, congenital diseases (eg, surgery for cardiopathy, congenital diaphragmatic hernia, or esophageal atresia), or other diseases. Clinical characteristics at birth, as well as characteristics at the moment of TDM were extracted from the patient files. We aimed to document early vancomycin exposure, therefore only first trough levels were included. Serum vancomycin assay was performed either with a particle-enhanced turbidimetric inhibitionimmunoassay method (Siemens Dimension; Dade Behring, Deerfield, Illinois–PETINIA) or with an enzyme multiplied immunoassay technique (Cobas c702; Roche Diagnostics, Basel, Germany–COBAS). The data were analyzed by Chi-square test, t test and Mann-Whitney U test. Linear Mix Model was used to assess significant differences between groups, when adjusting for confounding factors. Data were analyzed in SPSS 20.0 (IBM corp.), p-value <0.05 was significant. Results: In total, 564 vancomycin TDM observations, 311 assayed with PETINIA and 253 with COBAS, were included. Both cohorts had comparable clinical characteristics (median [min-max] current weight 2150 [420–5000] grams for PETINIA vs. 2120 [500–5840] grams for COBAS, and median postmenstrual age 35 [25–58] weeks for PETINIA vs. 35 [25–51] weeks for COBAS). We determined the significant difference between the vancomycin concentrations using two different immunoassays: PETINIA vs. COBAS (F=17.971; p<0.001). When adjusting for current body weight and postmenstrual age, the major covariates associated with vancomycin serum trough levels in neonates, the difference in vancomycin concentration between cohorts was statistically significant (F=17.076, p<0.001, F=18.951, p<0.001, respectively). Overall, immunoassays PETINIA and COBAS significantly differed by vancomycin concentrations when adjusting for covariates, and the mean difference for vancomycin concentration was 2.167 mg/l. Conclusion: The present study confirms the impact of assays on the variability in vancomycin concentration in neonates in a single NICU. Comparison between these two immunoassays showed a mean proportional differences >20%. Therefore, it is important to know how the vancomycin is measured when interpreting results, and particularly the transferability of vancomycin results between the laboratories has to be interpreted with caution.